Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Occurrence and risk assessment of antibiotic residues in Mediterranean olive grove soils with different management: an EU-wide pilot study - Andrés J. Rascón; Alfonso Fernández-García; David Moreno-Gónzalez; Bienvenida Gilbert-López; Antonio J. Manzaneda; Juan F. García-Reyes (Environmental Research, 2026)

Resilience in the face of climate change temporalities: dynamic processes in coastal social–ecological systems - Élise Lacoste; Hélène Rey-Valette; Valérie Derolez; Stéphane Ghiotti; Frédérique Viard; Esméralda Longépée; Adrien Chevallier; Gilbert David; Pierre Maurel; Romain Pete; Anliati Ahmed Abdallah; Patrick Monfort; et al. (Regional Environmental Change, 2026)

Introduced or established? Convergent evidence indicates imported pine wood nematode vectors occupy gaps in native distribution - Jean-Claude Grégoire; Jean Artois; Julien Claude; Marius Gilbert; Serge Morand; Géraldine Roux; Gilles San Martin; Dimitrios Avtzis; Nick Berkvens; Jochem Bonte; Hans Casteels; Sandra Closa; et al. (Journal of Pest Science, 2026)
Monitoring regulated quarantine plant pathogens and, when relevant, their vectors is compulsory in the European Union. Local Monochamus species (Coleoptera, Cerambycidae) vector the pine wood nematode, Bursaphelenchus xylophilus , a non-native pest already established in most of Portugal. Only 29 M. galloprovincialis individuals were trapped in Belgium in ten years (2013–2022), despite a dense coverage of pheromone-baited traps, suggesting absence or a very rare local occurrence in the country. In the northern neighbouring countries, only one single established population is known in The Netherlands and one in Denmark. A species distribution model based on pheromone-trap catches (negative and positive) of M. galloprovincialis from 4,914 traps in 29 European countries between 2008 and 2019 was developed, using the overall climate conditions and the distribution of seven pine tree species as explanatory variables. The effect of spatial scale was tested with a multi-scale approach. With a 225*225 km spatial grain, the major explanatory variables were the mean diurnal temperature range and, to a lesser extent, the presence of Pinus spp. The model predicted a low probability of presence in Belgium, the Netherlands, Great Britain and north-western Germany compared to southern Europe. Genotyping allowed to conclude that at least some of the beetles caught in Belgium originated from foreign locations. All catches were located close to entry points, suggesting introduction with imported material. The small size of most of the Belgian pine stands may also explain the absence or apparently transient status, or rareness of Monochamus spp. This study thus suggests that surveys in Belgium should privilege entry points rather than local forest stands.

Ecological and Social Surveys Uncover Gaps in Community-Based and Customary Mangrove Forest Management and Governance in Madagascar - Heritiana Alexis Randrianiaina; Behara Satyanarayana; Gilbert David; Jean Hugé; Farid Dahdouh-Guebas (Ethnobotany and Economic Botany, 2026)

Report of the scientific network Holimitox on succinate dehydrogenase inhibitor (SDHI) pesticides: new insights and challenges with an EcoHealth approach—presentations and round tables from the Holimitox day on November 7, 2024 - Jean-Marc Bonmatin; François Chamaraux; Séverine Jean; Emmanuella Abbey; Erwan Bézard; Lucie Bouly; Bénédicte Buffin-Meyer; Marie Buleon; Thomas Castellino; Frédéric Delbac; David Demortain; Colette Denis; et al. (Environmental Science and Pollution Research, 2026)

Temporal and spatial drivers of Lyme disease hazard differ between urban and rural environments - Sara L. Gandy; Jessica Hall; Grace Plahe; David Johnson; Richard Birtles; Lucy Gilbert (Landscape and Urban Planning, 2026)

Machine learning-based modeling of groundwater recharge under three climate change scenarios in the Densu Basin of Ghana, West Africa - Gilbert Jesse; Cyril D. Boateng; Jeffrey N.A. Aryee; Marian A. Osei; Michael Baidu; David D. Wemegah; Solomon S.R. Gidigasu; Samuel K. Afful (Groundwater for Sustainable Development, 2026)

PQRI Workshop: Model-Informed Drug Development (MIDD) Approaches in Pediatric Formulation Development - Gilbert J. Burckart; Susan Abdel-Rahman; Caleb Choi; M. Petrea Cober; James E. Cummins; Nikoletta Fotaki; Daniel Gonzalez; David Harris; Neil Parrott; Hardikkumar Patel; Fang Wu; Andreas Abend (The AAPS Journal, 2026)
In February of 2024, the Product Quality Research Institute held a virtual workshop entitled “Model-Informed Drug Development (MIDD) Approaches in Pediatric Formulation Development.” The workshop covered a range of topics related to pediatric formulation development and testing, including dissolution testing and applications to modeling drug absorption in developing pediatric patients. Workshop speakers reviewed the progress that has been made to advance our understanding of ontogeny related processes that drive interactions with product formulations and inform pediatric product development. They discussed recently constructed pediatric biorelevant models that provide more realistic information about drug dissolution in pediatric patients and their use in physiologically based models to produce data for regulatory submissions. Despite the progress, opportunities remain to expand the fund of knowledge on pediatric absorptive processes that will support the development of pediatric-friendly drug formulations. Graphical Abstract

Unlearned responses of chicks, Gallus gallus domesticus, towards aposematic insect-like stimuli - Christopher H. Taylor; David J.G. Watson; Francis Gilbert; David J. Pritchard; John Skelhorn; Tom Reader (Animal Behaviour, 2026)

PTUPB improves cognitive function in Alzheimer’s disease associated with enhancing cerebral vascular myogenic response and attenuating vascular remodeling - Gilbert C. Morgan; Andrew Gregory; Chengyun Tang; Sung Hee Hwang; Jane J. Border; Jing Xu; Yedan Liu; Shan Bai; Tae Jin Lee; Cameron Cantwell; David Bunn; Karen M. Wagner; et al. (GeroScience, 2026)

Assessment of exposure to pesticides, anticoagulant rodenticides, and PFASs in the blood of top-predator birds by LC-MS/MS analysis - Alfonso Fernández-García; Francisco M. Camacho; David Moreno-González; Ana B. Martínez-Piernas; Bienvenida Gilbert-López; Juan F. García-Reyes (Environmental Research, 2026)

Digestion of food proteins: the role of pepsin - Mengxiao Yang; Zhi Yang; David W. Everett; Elliot Paul Gilbert; Harjinder Singh; Aiqian Ye (Critical Reviews in Food Science and Nutrition, 2025)

Rugged LC-MS/MS method for the large-scale monitoring of glyphosate and other highly polar pesticides in soils across European Union olive orchards - Alfonso Fernández-García; David Moreno-González; Andrés J. Rascón; Ana B. Martínez-Piernas; Bienvenida Gilbert-López; Antonio J. Manzaneda; Juan F. García-Reyes (Environmental Pollution, 2025)

Production of natural products by using plant cell cultures as chemical factories - Gilbert Gorr; David A. Ullisch; Thomas Leibold (Phytochemistry Letters, 2025)

Climate Consideration in Environmental Effects Analyses on Federal Public Lands in the United States - Sarah E. Whipple; Sarah K. Carter; Tait K. Rutherford; Samuel E. Jordan; Richard J. Lehrter; Christopher T. Domschke; Megan A. Gilbert; Julian Reyes; Ella M. Samuel; Karen M. Schank; John C. Tull; David J. A. Wood (Environmental Management, 2025)

Apatite in situ Lu-Hf and U-Pb geochronology in layered mafic intrusions - Melissa Kharkongor; Stijn Glorie; Adam Abersteiner; Sarah Dare; Christopher Kirkland; David Chew; Jacob Mulder; Sarah Gilbert (Geochimica et Cosmochimica Acta, 2025)

Migratory Arctic char ( Salvelinus alpinus ) as a prey pulse for Arctic marine predators - Matthew J. H. Gilbert; Les N. Harris; Alexander L. Vail; Kristin L. Laidre; Mark L. Mallory; David J. Yurkowski (Ecology, 2025)

Historical genomic variation of Eurasian otters (Lutra lutra) in Britain, from hunting trophies - Sarah J. du Plessis; Nuno F. Martins; Xin Sun; Sarah S. T. Mak; David W. G. Stanton; Klaus-Peter Koepfli; Elizabeth A. Chadwick; M. P. Thomas Gilbert; Frank Hailer (Conservation Genetics Resources, 2025)
Genomic data from historical specimens can provide insights into populations and processes no longer evident from modern samples. Identifying viable sources of historical DNA is key to this. Here we aimed to explore the viability of trophy hunting paws as sources of historical DNA, and to use this data for preliminary analyses to evaluate changes in population structuring over time. We aimed to search for the presence of genomic signals of the putative recent introduction of Eurasian otters ( Lutra lutra ) from Asia to the UK previously identified using modern data, by analysis of two trophy paws from 1929 to 1952. Substantial proportions of endogenous DNA (77–85%) were identified in both samples for which genomic DNA extraction and sequencing was attempted, illustrating the potential of such specimens for historical DNA research. Autosomal variation suggests that the historical specimens cluster closest to modern specimens from Wales, and not with the variation identified in the East of England, putatively associated with the recent introduction of Eurasian otters from Asia. Similarly, the divergent mitochondrial lineage found in modern otters from the East of England and Asia, was not found in the historical British specimens. Although limited inferences can be made from a sample size of two, this preliminary dataset indicates the huge potential of historical trophy paw samples to assess past population genetic dynamics, calling for further research in this area.

Resilient plants, sustainable future - Seung Y. Rhee; Daniel N. Anstett; Edgar B. Cahoon; Alejandra A. Covarrubias-Robles; Eric Danquah; Natalia Dudareva; Hiroshi Ezura; Kadeem J. Gilbert; Rodrigo A. Gutiérrez; Michelle Heck; David B. Lowry; Ron Mittler; et al. (Trends in Plant Science, 2025)

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Dephasing of islet building between leeward and windward reef-rim sides, Bora Bora Island, Society Archipelago, central South Pacific - Lucien F. Montaggioni; Bernard Salvat; Edwige Pons-Branchu; Bertrand Martin-Garin; Gilbert Poli; Marie-Thérèse Vénec-Peyré; David Lecchini; Gaston Tong Sang (Quaternary International, 2025)

Probing structural modification of milk proteins in the presence of pepsin and/or acid using small- and ultra-small-angle neutron scattering - Mengxiao Yang; Aiqian Ye; Zhi Yang; David W. Everett; Liliana de Campo; Harjinder Singh; Elliot Paul Gilbert (Food Hydrocolloids, 2025)

Host Species–Microbiome Interactions Contribute to Sphagnum Moss Growth Acclimation to Warming - Tatjana Živković; Alyssa A. Carrell; Gustaf Granath; A. Jonathan Shaw; Dale A. Pelletier; Christopher W. Schadt; Dawn M. Klingeman; Mats B. Nilsson; Manuel Helbig; Denis Warshan; Ingeborg J. Klarenberg; Daniel Gilbert; et al. (Global Change Biology, 2025)
Sphagnum moss is the dominant plant genus in northern peatlands responsible for long‐term carbon accumulation. Sphagnum hosts diverse microbial communities (microbiomes), and its phytobiome (plant host + constituent microbiome + environment) plays a key role in nutrient acquisition along with carbon cycling. Climate change can modify the Sphagnum ‐associated microbiome, resulting in enhanced host growth and thermal acclimation as previously shown in warming experiments. However, the extent of microbiome benefits to the host and the influence of host–microbe specificity on Sphagnum thermal acclimation remain unclear. Here, we extracted Sphagnum microbiomes from five donor species of four peatland warming experiments across a latitudinal gradient and applied those microbiomes to three germ‐free Sphagnum species grown across a range of temperatures in the laboratory. Using this experimental system, we test if Sphagnum 's growth response to warming depends on the donor and/or recipient host species, and we determine how the microbiome's growth conditions in the field affect Sphagnum host growth across a range of temperatures in the laboratory. After 4 weeks, we found that the highest growth rate of recipient Sphagnum was observed in treatments of matched host–microbiome pairs, with rates approximately 50% and 250% higher in comparison to maximum growth rates of non‐matched host–microbiome pairs and germ‐free Sphagnum , respectively. We also found that the maximum growth rate of host–microbiome pairs was reached when treatment temperatures were close to the microbiome's native temperatures. Our study shows that Sphagnum 's growth acclimation to temperature is partially controlled by its constituent microbiome. Strong Sphagnum host–microbiome species specificity indicates the existence of underlying, unknown physiological mechanisms that may drive Sphagnum 's ability to acclimatize to elevated temperatures. Together with rapid acclimation of the microbiome to warming, these specific microbiome–plant associations have the potential to enhance peatland resilience in the face of climate change.

Chemical profiling of organic contaminants in rural surface waters combining target and non-target LC-HRMS/MS analysis - Alfonso Fernández-García; Ana B. Martínez-Piernas; David Moreno-González; Bienvenida Gilbert-López; Juan F. García-Reyes (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Genome‐wide population affinities and signatures of adaptation in hydruntines, sussemiones and Asian wild asses - Jianfei Pan; Xuexue Liu; Mateusz Baca; Laure Calvière‐Tonasso; Stéphanie Schiavinato; Loreleï Chauvey; Gaétan Tressières; Aude Perdereau; Jean‐Marc Aury; Pedro H. Oliveira; Patrick Wincker; Aida Abdykanova; et al. (Molecular Ecology, 2024)
The extremely rich palaeontological record of the horse family, also known as equids, has provided many examples of macroevolutionary change over the last ~55 Mya. This family is also one of the most documented at the palaeogenomic level, with hundreds of ancient genomes sequenced. While these data have advanced understanding of the domestication history of horses and donkeys, the palaeogenomic record of other equids remains limited. In this study, we have generated genome‐wide data for 25 ancient equid specimens spanning over 44 Ky and spread across Anatolia, the Caucasus, Central Asia and Mongolia. Our dataset includes the genomes from two extinct species, the European wild ass, Equus hydruntinus , and the sussemione Equus ovodovi . We document, for the first time, the presence of sussemiones in Mongolia and their survival around ~3.9 Kya, a finding that should be considered when discussing the timing of the first arrival of the domestic horse in the region. We also identify strong spatial differentiation within the historical ecological range of Asian wild asses, Equus hemionus , and incomplete reproductive isolation in several groups yet considered as different species. Finally, we find common selection signatures at ANTXR2 gene in European, Asian and African wild asses. This locus, which encodes a receptor for bacterial toxins, shows no selection signal in E. ovodovi , but a 5.4‐kb deletion within intron 7. Whether such genetic modifications played any role in the sussemione extinction remains unknown.

Sitka black-tailed deer habitat selection in relation to logging and vegetation in a temperate rainforest - David P. Gregovich; Gretchen H. Roffler; Christina M. Prokopenko; Sophie L. Gilbert (Forest Ecology and Management, 2024)

Crops production and the contribution of agricultural biomass power generation to Africa's clean energy transition: Analysis of trends from 1990 to 2021 - Augustine Awaafo; Edward A. Awafo; Meisam Mahdavi; Gilbert Akolgo; Francisco Jurado; David Vera; Emmanuel Amankwah (Biomass and Bioenergy, 2024)

A multispecies hierarchical model to integrate count and distance‐sampling data - Neil A. Gilbert; Caroline M. Blommel; Matthew T. Farr; David S. Green; Kay E. Holekamp; Elise F. Zipkin (Ecology, 2024)
Integrated community models—an emerging framework in which multiple data sources for multiple species are analyzed simultaneously—offer opportunities to expand inferences beyond the single‐species and single‐data‐source approaches common in ecology. We developed a novel integrated community model that combines distance sampling and single‐visit count data; within the model, information is shared among data sources (via a joint likelihood) and species (via a random‐effects structure) to estimate abundance patterns across a community. Parameters relating to abundance are shared between data sources, and the model can specify either shared or separate observation processes for each data source. Simulations demonstrated that the model provided unbiased estimates of abundance and detection parameters even when detection probabilities varied between the data types. The integrated community model also provided more accurate and more precise parameter estimates than alternative single‐species and single‐data‐source models in many instances. We applied the model to a community of 11 herbivore species in the Masai Mara National Reserve, Kenya, and found considerable interspecific variation in response to local wildlife management practices: Five species showed higher abundances in a region with passive conservation enforcement (median across species: 4.5× higher), three species showed higher abundances in a region with active conservation enforcement (median: 3.9× higher), and the remaining three species showed no abundance differences between the two regions. Furthermore, the community average of abundance was slightly higher in the region with active conservation enforcement but not definitively so (posterior mean: higher by 0.20 animals; 95% credible interval: 1.43 fewer animals, 1.86 more animals). Our integrated community modeling framework has the potential to expand the scope of inference over space, time, and levels of biological organization, but practitioners should carefully evaluate whether model assumptions are met in their systems and whether data integration is valuable for their applications.

Occurrence and risk assessment of pesticides and their transformation products related to olive groves in surface waters of the Guadalquivir river basin - Alfonso Fernández-García; Ana B. Martínez-Piernas; David Moreno-González; Bienvenida Gilbert-López; Antonio Molina-Díaz; Juan F. García-Reyes (Chemosphere, 2024)

Pepsin-induced hydrolysis and coagulation of proteins in goat, sheep and cow milk - Mengxiao Yang; Aiqian Ye; Elliot Paul Gilbert; Zhi Yang; David W. Everett; Harjinder Singh (International Dairy Journal, 2024)

Home range and resource selection of Virginia opossums in the rural southeastern United States - Jacob E. Hill; David A. Bernasconi; Richard B. Chipman; Amy T. Gilbert; James C. Beasley; Olin E. Rhodes; Guha Dharmarajan (Mammal Research, 2024)

Background contrast affects detection and recognition of courting wolf spiders by intended and unintended receivers - George W. Uetz; Rachel Gilbert; Rebecca Wilson; Jacqueline Mann; Joseph Macedonia; David L. Clark (Behavioral Ecology and Sociobiology, 2024)
We used video playback of courting male Schizocosa ocreata wolf spiders to examine responses of intended receivers (conspecific females) and eavesdroppers (competitor males, predatory spiders, toads) to manipulations of spider color (natural color, monochromatic gray, monochromatic RBG average) displayed against complex leaf litter backgrounds (color, grayscale). Models of chromatic and achromatic contrast between spider stimuli and backgrounds were used to predict receiver responses. The results support the hypothesis that interactions between spider and background coloration affect detection and recognition, although responses varied with receiver type. Detection responses of intended receivers (female S. ocreata ) did not fit predictions of the chromatic contrast model in some cases, but showed a fair fit to the achromatic model. Detection responses of social eavesdroppers (male S. ocreata ) fit the chromatic and achromatic contrast models slightly better than did female responses (poor fit and very good fit, respectively). Eavesdropping wolf spider predators ( Rabidosa ) exhibited detection responses that significantly matched predictions of the chromatic (very good fit) and achromatic (excellent fit) models. Whereas jumping spiders ( Phidippus ) showed a good fit to the chromatic and achromatic contrast models, toad predators had a good fit only to the chromatic model. Recognition responses revealed a different pattern of fit to the chromatic and achromatic models across receiver types, although Rabidosa again indicated a significant fit to both models. Taken together, the results of this study identify both chromatic and achromatic features of spider appearance as likely explanations for differences in behavioral responses of intended and unintended receivers. This outcome suggests the possibility that both sexual and natural selection likely target different features of male appearance during courtship.

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Fish shrinking, energy balance and climate change - Quentin Queiros; David J. McKenzie; Gilbert Dutto; Shaun Killen; Claire Saraux; Quentin Schull (Science of The Total Environment, 2024)

Hydrodynamic response to bathymetric changes in Tampa Bay, Florida - Jing Chen; Yonggang Liu; Robert H. Weisberg; Steven A. Murawski; Sherryl Gilbert; David F. Naar; Lianyuan Zheng; Matthew Hommeyer; Catherine Dietrick; Mark E. Luther; Cheryl Hapke; Edward Myers; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Periconceptional and Prenatal Exposure to Metals and Extracellular Vesicle and Particle miRNAs in Human Milk: A Pilot Study - Caitlin G. Howe; David A. Armstrong; Meghan E. Muse; Diane Gilbert-Diamond; Jiang Gui; Anne G. Hoen; Thomas J. Palys; Roxanna L. Barnaby; Bruce A. Stanton; Brian P. Jackson; Brock C. Christensen; Margaret R. Karagas (Exposure and Health, 2023)

Towards translating in vitro measures of thyroid hormone system disruption to in vivo responses in the pregnant rat via a biologically based dose response (BBDR) model - Jeffrey Fisher; Conrad Housand; David Mattie; Andy Nong; Marjory Moreau; Mary Gilbert (Toxicology and Applied Pharmacology, 2023)

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

Operant novelty seeking predicts cue-induced reinstatement following cocaine but not water reinforcement in male rats - Amy M. Gancarz; Devin P. Hagarty; Moriah M. Cobb; Michael A. Kausch; Brandon Krieg; Nora Alammari; Kameron Gilbert; Jacqueline Russo; David M. Dietz (Psychopharmacology, 2023)
Rationale An important facet of cocaine addiction is a high propensity to relapse, with increasing research investigating factors that predispose individuals toward uncontrolled drug use and relapse. A personality trait linked to drug addiction is high sensation seeking, i.e., a preference for novel sensations/experiences. In an animal model of sensation seeking, operant novelty seeking predicts the acquisition of drug self-administration. Objective The primary goal of this research was to evaluate the hypothesis that sensitivity to the reinforcing effects of novel sensory stimuli predicts more intensive aspects of drug-taking behaviors, such as relapse. Methods Rats were first tested for Operant Novelty Seeking, during which responses resulted in complex visual/auditory stimuli. Next, rats were trained to respond to water/cocaine reinforcers signaled by a cue light. Finally, rats were exposed to extinction in the absence of discrete cues and subsequently tested in a single session of cue-induced reinstatement, during which active responses resulted in cues previously paired with water/cocaine delivery. Results The present study showed operant responses to produce novel sensory stimuli positively correlate with responding for cocaine during self-administration and during discrete cue-induced reinstatement, but no association with performance during extinction. A different pattern of associations was observed for a natural reward, in this case, water reinforcement. Here, the degree of novelty seeking also correlated with responding to water reinforcement and extinction responding; however, operant novelty seeking did not correlate with responding to water cues during testing of cue-induced reinstatement. Taken together, the incongruence of relationships indicates an underlying difference between natural and drug reinforcers. Conclusion In summary, we found a reinforcer-dependent relationship between operant novelty seeking (i.e., sensation seeking) and responsivity to extinction and discrete cues signaling availability for cocaine (i.e., craving), demonstrating the validity of the operant novelty seeking model to investigate drug seeking and relapse.

Organic carbon in British lowland ponds: estimating sediment stocks, possible practical benefits and significant unknowns - Michael J. Jeffries; Peter J. Gilbert; Scott Taylor; David A. Cooke; Michael E. Deary (Hydrobiologia, 2023)
Ponds are aquatic habitats defined by their small size. Although small they are found on every continent, they are disproportionately rich in aquatic biodiversity, benefit terrestrial wildlife and have important ecosystem function benefits. One of these benefits might be carbon sequestration, a possibility suggested by (1) their abundance, (2) the intensity of their biogeochemical activity. Whilst greenhouse gas fluxes from ponds have been monitored widely, quantifying the stocks of organic carbon buried in sediment is a gap in our knowledge. Here we summarise measures of organic carbon in pond sediments cores from a diverse range of lowland ponds in England. We estimate a general measure of 9.38 kg OC in a 1 m 2 × 20 cm block of pond sediment and scale this up to an overall estimate for Great Britain of 2.63 million tons of OC in pond sediment, with 95% CI of 1.41 to 3.84 million tons. The relationship between sediment carbon and gas fluxes remains a significant unknown.

Vulnerability and resilience of living marine resources to the Deepwater Horizon oil spill: an overview - Steven A. Murawski; Patrick T. Schwing; William F. Patterson; Tracey T. Sutton; Paul A. Montagna; Rosanna J. Milligan; Samantha B. Joye; Len Thomas; Joshua P. Kilborn; Claire B. Paris; Robin Faillettaz; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The 2010 Deepwater Horizon (DWH) oil well blowout in the Gulf of Mexico (GoM) was the largest and perhaps most consequential accidental marine oil spill in global history. This paper provides an overview of a Research Topic consisting of four additional papers that: (1) assemble time series data for ecosystem components in regions impacted by the spill, and (2) interpret temporal changes related to the vulnerability of species and ecosystems to DWH and the ensuing resilience to perturbation. Time series abundance data for many taxa pre-date DWH, often by decades, thus allowing an assessment of population- and community-level impacts. We divided the north central GoM into four interconnected “eco-types”: the coastal/nearshore, continental shelf, open-ocean pelagic and deep benthic. Key taxa in each eco-type were evaluated for their vulnerability to the circumstances of the DWH spill based on population overlap with oil, susceptibility to oil contamination, and other factors, as well their imputed resilience to population-level impacts, based on life history metrics, ecology and post-spill trajectories. Each taxon was scored as low, medium, or high for 13 vulnerability attributes and 11 resilience attributes to produce overall vulnerability and resilience scores, which themselves were also categorical (i.e., low, medium, or high). The resulting taxon-specific V-R scores provide important guidance on key species to consider and monitor in the event of future spills similar to DWH. Similar analyses may also guide resource allocation to collect baseline data on highly vulnerable taxa or those with low resilience potential in other ecosystems. For some species, even a decade of observation has been insufficient to document recovery given chronic, long-term exposure to DWH oil remaining in all eco-types and because of impacts to the reproductive output of long-lived species. Due to the ongoing threats of deep-water blowouts, continued surveillance of populations affected by DWH is warranted to document long-term recovery or change in system state. The level of population monitoring in the open-ocean and deep benthic eco-types has historically been low and is inconsistent with the continued migration of the oil industry to the ultra-deep (≥1,500 m) where the majority of leasing, exploration, and production now occurs.

Effect of ingestion temperature on the pepsin-induced coagulation and the in vitro gastric digestion behavior of milk - Mengxiao Yang; Aiqian Ye; Zhi Yang; David W. Everett; Elliot Paul Gilbert; Harjinder Singh (Food Hydrocolloids, 2023)

Genomic diversity and differentiation between island and mainland populations of white‐tailed eagles ( Haliaeetus albicilla ) - Charles Christian Riis Hansen; Áki Jarl Láruson; Jacob Agerbo Rasmussen; Jesus Adrian Chimal Ballesteros; Mikkel‐Holger S. Sinding; Gunnar T. Hallgrimsson; Menja von Schmalensee; Robert A. Stefansson; Kristinn Haukur Skarphédinsson; Aili Lage Labansen; Madis Leivits; Christian Sonne; et al. (Molecular Ecology, 2023)
Divergence in the face of high dispersal capabilities is a documented but poorly understood phenomenon. The white‐tailed eagle ( Haliaeetus albicilla ) has a large geographic dispersal capability and should theoretically be able to maintain genetic homogeneity across its dispersal range. However, following analysis of the genomic variation of white‐tailed eagles, from both historical and contemporary samples, clear signatures of ancient biogeographic substructure across Europe and the North‐East Atlantic is observed. The greatest genomic differentiation was observed between island (Greenland and Iceland) and mainland (Denmark, Norway and Estonia) populations. The two island populations share a common ancestry from a single mainland population, distinct from the other sampled mainland populations, and despite the potential for high connectivity between Iceland and Greenland they are well separated from each other and are characterized by inbreeding and little variation. Temporal differences also highlight a pattern of regional populations persisting despite the potential for admixture. All sampled populations generally showed a decline in effective population size over time, which may have been shaped by four historical events: (1) Isolation of refugia during the last glacial period 110–115,000 years ago, (2) population divergence following the colonization of the deglaciated areas ~10,000 years ago, (3) human population expansion, which led to the settlement in Iceland ~1100 years ago, and (4) human persecution and exposure to toxic pollutants during the last two centuries.

Multiple‐brooding rockfishes ( Sebastes spp.) can utilize stored sperm from individual sires to fertilize consecutive broods - Neosha S Kashef; David M. Stafford; Susan M. Sogard; John C. Garza; John C. Field; Elizabeth A. Gilbert‐Horvath (Journal of Fish Biology, 2023)
Viviparous rockfishes ( Sebastes spp., family Scorpaenidae) mate and store sperm in the ovaries for several months prior to fertilization, as oocytes develop for the parturition season. Although multiple paternity has been documented in single‐brooding rockfishes, paternity in consecutive broods of multiple‐brooding species has not been studied. Analyses of multilocus microsatellite genotypes in both residual larvae left in the ovary from a previous parturition and upcoming fertilized broods in the same ovary demonstrated evidence of the same sires in consecutive broods in chilipepper ( Sebastes goodei ) and speckled ( Sebastes ovalis ) rockfishes. One S. goodei mother showed evidence of multiple paternity from the same two sires in both consecutive broods. The ability to retain sperm, even after a parturition event, for use in subsequent broods, confers an advantage to ensure fertilization and allows for extension of the parturition season. This life‐history strategy provides a bet‐hedging advantage in the California Current system, an environmentally dynamic ecosystem where larval survivorship and subsequent recruitment to adult populations can vary temporally by orders of magnitude.

Pepsin-induced coagulation of casein micelles: Effect of whey proteins and heat treatment - Mengxiao Yang; Aiqian Ye; Zhi Yang; David W. Everett; Elliot Paul Gilbert; Harjinder Singh (Food Chemistry, 2023)

Limited recovery following a massive seagrass decline in subarctic eastern Canada - Mélanie‐Louise Leblanc; Mary I. O'Connor; Zou Zou A. Kuzyk; Fanny Noisette; Kaleigh E. Davis; Ernie Rabbitskin; Laura‐Lee Sam; Urs Neumeier; Rémi Costanzo; Jens K. Ehn; David Babb; C. Julián Idrobo; et al. (Global Change Biology, 2023)
Over the last few decades, there has been an increasing recognition for seagrasses' contribution to the functioning of nearshore ecosystems and climate change mitigation. Nevertheless, seagrass ecosystems have been deteriorating globally at an accelerating rate during recent decades. In 2017, research into the condition of eelgrass ( Zostera marina ) along the eastern coast of James Bay, Canada, was initiated in response to reports of eelgrass decline by the Cree First Nations of Eeyou Istchee. As part of this research, we compiled and analyzed two decades of eelgrass cover data and three decades of eelgrass monitoring data (biomass and density) to detect changes and assess possible environmental drivers. We detected a major decline in eelgrass condition between 1995 and 1999, which encompassed the entire east coast of James Bay. Surveys conducted in 2019 and 2020 indicated limited changes post‐decline, for example, low eelgrass cover ( 50% cover in eastern James Bay since 1995, representing the largest scale eelgrass decline documented in eastern Canada since the massive die‐off event that occurred in the 1930s along the North Atlantic coast. Using biomass data collected since 1982, but geographically limited to the sector of the coast near the regulated La Grande River, generalized additive modeling revealed eelgrass meadows are affected by local sea surface temperature, early ice breakup, and higher summer freshwater discharge. Our results caution against assuming subarctic seagrass ecosystems have avoided recent global declines or will benefit from ongoing climate warming.

“Draw the sea…”: Children’s representations of ocean connectivity in Fiji and New Caledonia - Elodie Fache; Susanna Piovano; Alisi Soderberg; Malakai Tuiono; Léa Riera; Gilbert David; Matthias Kowasch; Simonne Pauwels; Annette Breckwoldt; Stéphanie M. Carrière; Catherine Sabinot (Ambio, 2022)
In the South Pacific region, marine territories and resources play a crucial role for local communities. Children engage with these territories and resources from an early age onwards. As the next ocean stewards, they are a stakeholder group whose understandings of ocean connectivity and fisheries should be given serious consideration in decision-making processes towards the sustainable use and management of coastal seas. This paper analyses 290 children’s drawings from Fiji and New Caledonia, created in 2019 in spontaneous response to the instruction: “Draw the sea and what you and others do in the sea”. Exploring the webs of connections with and within the sea revealed by these children’s drawings and their own interpretations leads us to discuss children’s representations of the sea: (1) beyond a land-sea compartmentation, (2) as a locus of both exploitation and conservation of marine life, and (3) as a ‘place-full’ space connecting human and more-than-human realms.

A social-ecological engagement with reef passages in New Caledonia: Connectors between coastal and oceanic spaces and species - Annette Breckwoldt; Yvy Dombal; Catherine Sabinot; Gilbert David; Léa Riera; Sebastian Ferse; Elodie Fache (Ambio, 2022)
Healthy and protected coral reefs help island systems in the tropics thrive and survive. Reef passages link the open ocean to lagoon and coastal areas in these ecosystems and are home to an exceptionally diverse and abundant marine life, hosting emblematic species and fish spawning aggregations. Their multiple benefits for the islands and their peoples (e.g., for transport, fishing, socio-cultural aspects) remain yet understudied. Drawing from qualitative interviews with fishers, scuba divers, and surfers along the coast of Grande Terre in New Caledonia, this study highlights the multi-faceted importance of these keystone places. It shows that reef passages are locally deemed ‘communication zones’ between coastal and oceanic spaces and species, and have significant un(der)explored ecological and socio-cultural roles. Understanding and protecting these ecological and cultural keystone places will strengthen both the reef ecosystems and the people dependent on them.

Correction to: Tracking the history of grapevine cultivation in Georgia by combining geometric morphometrics and ancient DNA - Laurent Bouby; Nathan Wales; Mindia Jalabadze; Nana Rusishvili; Vincent Bonhomme; Jazmín Ramos‑Madrigal; Allowen Evin; Sarah Ivorra; Thierry Lacombe; Clémence Pagnoux; Elisabetta Boaretto; M. Thomas P. Gilbert; et al. (Vegetation History and Archaeobotany, 2022)

Baited video reveal fish diversity in the vast inter-reef habitats of a marine tropical lagoon - Florian Baletaud; Antoine Gilbert; David Mouillot; Jean-Marie Come; Laurent Vigliola (Marine Biodiversity, 2022)

Sorbents for treatment of hereditary hemochromatosis - Anna Wilson; Leslie Laguna; Lansten Yew; Kerry Kao; Kathryn Bauguess; Jiaying Wang; Sofia de la O; Grant Romme; William Gilbert; Ana Rita C. Morais; Jian Qian; Cory J. Berkland; et al. (Medicinal Chemistry Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Predicting moisture content during maize nixtamalization using machine learning with NIR spectroscopy - Michael J. Burns; Jonathan S. Renk; David P. Eickholt; Amanda M. Gilbert; Travis J. Hattery; Mark Holmes; Nickolas Anderson; Amanda J. Waters; Sathya Kalambur; Sherry A. Flint-Garcia; Marna D. Yandeau-Nelson; George A. Annor; et al. (Theoretical and Applied Genetics, 2021)

Leech blood‐meal invertebrate‐derived DNA reveals differences in Bornean mammal diversity across habitats - Rosie Drinkwater; Tommaso Jucker; Joshua H. T. Potter; Tom Swinfield; David A. Coomes; Eleanor M. Slade; M. Thomas P. Gilbert; Owen T. Lewis; Henry Bernard; Matthew J. Struebig; Elizabeth L. Clare; Stephen J. Rossiter (Molecular Ecology, 2021)
The application of metabarcoding to environmental and invertebrate‐derived DNA (eDNA and iDNA) is a new and increasingly applied method for monitoring biodiversity across a diverse range of habitats. This approach is particularly promising for sampling in the biodiverse humid tropics, where rapid land‐use change for agriculture means there is a growing need to understand the conservation value of the remaining mosaic and degraded landscapes. Here we use iDNA from blood‐feeding leeches ( Haemadipsa picta ) to assess differences in mammalian diversity across a gradient of forest degradation in Sabah, Malaysian Borneo. We screened 557 individual leeches for mammal DNA by targeting fragments of the 16S rRNA gene and detected 14 mammalian genera. We recorded lower mammal diversity in the most heavily degraded forest compared to higher quality twice logged forest. Although the accumulation curves of diversity estimates were comparable across these habitat types, diversity was higher in twice logged forest, with more taxa of conservation concern. In addition, our analysis revealed differences between the community recorded in the heavily logged forest and that of the twice logged forest. By revealing differences in mammal diversity across a human‐modified tropical landscape, our study demonstrates the value of iDNA as a noninvasive biomonitoring approach in conservation assessments.

APOE genotype influences P3b amplitude and response to smoking abstinence in young adults - Ryan Coppens; Norka E. Rabinovich; Raghuveer Kanneganti; Herman A. Diggs; Kristin Wiggs; Travis Healey; Jodi Huggenvik; Gregory M. Rose; David G. Gilbert (Psychopharmacology, 2021)

Altered frontal-mediated inhibition and white matter connectivity in pediatric chronic tic disorders - Adrienne B. Bruce; Weihong Yuan; Donald L. Gilbert; Paul S. Horn; Hannah S. Jackson; David A. Huddleston; Steve W. Wu (Experimental Brain Research, 2021)

Oxygen uptake, heart rate and activities of locomotor muscles during a critical swimming speed protocol in the gilthead sea bream Sparus aurata - Mouniboudine Hachim; Tristan Rouyer; Gilbert Dutto; Vincent Kerzerho; Serge Bernard; Jérôme Bourjea; David J. McKenzie (Journal of Fish Biology, 2021)
Oxygen uptake, heart rate and contraction frequencies of slow oxidative (SO) and fast glycolytic (FG) muscle were measured simultaneously in gilthead seabream Sparus aurata submitted to stepwise increases in current speed in a swimming respirometer. Variation in oxygen uptake was closely related to variation in heart rate, over initial steps these rose in concert with an increase in contraction frequency of SO muscle. There was an asymptote in oxygen uptake and heart rate at high speeds that reflected a transition from exclusive use of aerobic SO muscle to a combination of SO and anaerobic FG muscle, and which preceded fatigue.

Mycorrhizal type influences plant density dependence and species richness across 15 temperate forests - Feng Jiang; James A. Lutz; Qingxi Guo; Zhanqing Hao; Xugao Wang; Gregory S. Gilbert; Zikun Mao; David A. Orwig; Geoffrey G. Parker; Weiguo Sang; Yankun Liu; Songyan Tian; et al. (Ecology, 2021)
Recent studies suggest that the mycorrhizal type associated with tree species is an important trait influencing ecological processes such as response to environmental conditions and conspecific negative density dependence (CNDD). However, we lack a general understanding of how tree mycorrhizal type influences CNDD strength and the resulting patterns of species abundance and richness at larger spatial scales. We assessed 305 species across 15 large, stem‐mapped, temperate forest dynamics plots in Northeastern China and North America to explore the relationships between tree mycorrhizal type and CNDD, species abundance, and species richness at a regional scale. Tree species associated with arbuscular mycorrhizal (AM) fungi showed a stronger CNDD and a more positive relationship with species abundance than did tree species associated with ectomycorrhizal (ECM) fungi. For each plot, both basal area and stem abundance of AM tree species was lower than that of ECM tree species, suggesting that AM tree species were rarer than ECM tree species. Finally, ECM tree dominance showed a negative effect on plant richness across plots. These results provide evidence that tree mycorrhizal type plays an important role in influencing CNDD and species richness, highlighting this trait as an important factor in structuring plant communities in temperate forests.

Tracking the history of grapevine cultivation in Georgia by combining geometric morphometrics and ancient DNA - Laurent Bouby; Nathan Wales; Mindia Jalabadze; Nana Rusishvili; Vincent Bonhomme; Jazmín Ramos-Madrigal; Allowen Evin; Sarah Ivorra; Thierry Lacombe; Clémence Pagnoux; Elisabetta Boaretto; M. Thomas P. Gilbert; et al. (Vegetation History and Archaeobotany, 2021)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Coronavirus surveillance of wildlife in the Lao People’s Democratic Republic detects viral RNA in rodents - David J. McIver; Soubanh Silithammavong; Watthana Theppangna; Amethyst Gillis; Bounlom Douangngeun; Kongsy Khammavong; Sinpakone Singhalath; Veasna Duong; Philippe Buchy; Sarah H. Olson; Lucy Keatts; Amanda E. Fine; et al. (Archives of Virology, 2020)

Nicotine patch for cannabis withdrawal symptom relief: a randomized controlled trial - David G. Gilbert; Norka E. Rabinovich; Justin T. McDaniel (Psychopharmacology, 2020)

Effects of the Bioturbating Marine Yabby Trypaea australiensis on Sediment Properties in Sandy Sediments Receiving Mangrove Leaf Litter - Ryan J. K. Dunn; David T. Welsh; Peter R. Teasdale; Franck Gilbert; Jean-Christophe Poggiale; Nathan J. Waltham (Journal of Marine Science and Engineering, 2019)
Laboratory mesocosm incubations were undertaken to investigate the influence of burrowing shrimp Trypaea australiensis (marine yabby) on sediment reworking, physical and chemical sediment characteristics and nutrients in sandy sediments receiving mangrove (Avicennia marina) leaf litter. Mesocosms of sieved, natural T. australiensis inhabited sands, were continually flushed with fresh seawater and pre-incubated for 17 days prior to triplicates being assigned to one of four treatments; sandy sediment (S), sediment + yabbies (S+Y), sediment + leaf litter (organic matter; S+OM) and sediment + yabbies + leaf litter (S+Y+OM) and maintained for 55 days. Mangrove leaf litter was added daily to treatments S+OM and S+Y+OM. Luminophores were added to mesocosms to quantify sediment reworking. Sediment samples were collected after the pre-incubation period from a set of triplicate mesocosms to establish initial conditions prior to the imposition of the treatments and from the treatment mesocosms at the conclusion of the 55-day incubation period. Yabbies demonstrated a clear effect on sediment topography and leaf litter burial through burrow creation and maintenance, creating mounds on the sediment surface ranging in diameter from 3.4 to 12 cm. Within S+Y+OM sediments leaf litter was consistently removed from the surface to sub-surface layers with only 7.5% ± 3.6% of the total mass of leaf detritus added to the mesocosms remaining at the surface at the end of the 55-day incubation period. Yabbies significantly decreased sediment wet-bulk density and increased porosity. Additionally, T. australiensis significantly reduced sediment bio-available ammonium (NH4+bio) concentrations and altered the shape of the concentration depth profile in comparison to the non-bioturbated mesocosms, indicating influences on nutrient cycling and sediment-water fluxes. No significant changes for mean apparent biodiffusion coefficients (Db) and mean biotransport coefficients (r), were found between the bioturbated S+Y and S+Y+OM mesocosms. The findings of this study provide further evidence that T. australiensis is a key-species in shallow intertidal systems playing an important role as an ‘ecosystem engineer’ in soft-bottom habitats by significantly altering physical and chemical structures and biogeochemical function.

Characterization and detection of maize-associated pteridovirus (MaPV), infecting maize (Zea mays) in the Arusha region of Tanzania - David Alan Read; Jonathan Featherston; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingstone Mashingaidze; Gerhard Pietersen; Barnabas Kiula; Alois Kullaya; Ernest Mbega (European Journal of Plant Pathology, 2019)

Food in the Sea: Size Also Matters for Pelagic Fish - Quentin Queiros; Jean-Marc Fromentin; Eric Gasset; Gilbert Dutto; Camille Huiban; Luisa Metral; Lina Leclerc; Quentin Schull; David J. McKenzie; Claire Saraux (Frontiers in Marine Science, 2019)

Spatial ecology of urban striped skunks (Mephitis mephitis) in the Northern Great Plains: a framework for future oral rabies vaccination programs - Anna L. Schneider; Amy T. Gilbert; W. David Walter; Gregory S. Vandeberg; Jason R. Boulanger (Urban Ecosystems, 2019)

Diversity and distribution of Maize-associated totivirus strains from Tanzania - David Alan Read; Jonathan Featherston; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingstone Mashingaidze; Gerhard Pietersen; Barnabas Kiula; Alois Kullaya; Ernest R. Mbega (Virus Genes, 2019)

Molecular characterization of Morogoro maize-associated virus, a nucleorhabdovirus detected in maize (Zea mays) in Tanzania - David Alan Read; Jonathan Featherston; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingstone Mashingaidze; Gerhard Pietersen; Barnabas Kiula; Alois Kullaya; Ernest R. Mbega (Archives of Virology, 2019)

Mission-Specific Platforms - David McInroy; Gilbert Camoin (Oceanography, 2019)

First report of maize yellow mosaic virus (MaYMV) on maize (Zea mays) in Tanzania - David Alan Read; Jonathan Featherstone; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingston Mashingaidze; Dave Kenneth Berger; Tanya Welgemoed; Gerhard Pietersen; Susanna Elizabeth Schulze; Barnabas Kiula; et al. (Journal of Plant Pathology, 2019)

Predation drives recurrent convergence of an interspecies mutualism - William E. Feeney; Rohan M. Brooker; Lane N. Johnston; James D. J. Gilbert; Marc Besson; David Lecchini; Danielle L. Dixson; Peter F. Cowman; Andrea Manica (Ecology Letters, 2019)
Mutualisms are important ecological interactions that underpin much of the world's biodiversity. Predation risk has been shown to regulate mutualism dynamics in species‐specific case studies; however, we lack studies which investigate whether predation can also explain broader patterns of mutualism evolution. We report that fish‐anemone mutualisms have evolved on at least 55 occasions across 16 fish families over the past 60 million years and that adult body size is associated with the ontogenetic stage of anemone mutualisms: larger‐bodied species partner with anemones as juveniles, while smaller‐bodied species partner with anemones throughout their lives. Field and laboratory studies show that predators target smaller prey, that smaller fishes associate more with anemones, and that these relationships confer protection to small fishes. Our results indicate that predation is likely driving the recurrent convergent evolution of fish‐anemone mutualisms and suggest that similar ecological processes may have selected convergence in interspecies interactions in other animal clades.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Evaluation of eDNA for groundwater invertebrate detection and monitoring: a case study with endangered Stygobromus (Amphipoda: Crangonyctidae) - Matthew L. Niemiller; Megan L. Porter; Jenna Keany; Heather Gilbert; Daniel W. Fong; David C. Culver; Christopher S. Hobson; K. Denise Kendall; Mark A. Davis; Steven J. Taylor (Conservation Genetics Resources, 2018)

Sustainable livelihoods and effectiveness of disaster responses: a case study of tropical cyclone Pam in Vanuatu - Loïc Le Dé; Tony Rey; Frederic Leone; David Gilbert (Natural Hazards, 2018)

Developing new age-specific prostate-specific antigen thresholds for testing for prostate cancer - Rebecca Gilbert; Kate Tilling; Richard M. Martin; J. Athene Lane; Michael Davis; Freddie C. Hamdy; David E. Neal; Jenny L. Donovan; Chris Metcalfe (Cancer Causes & Control, 2018)

An Improved Reconstruction of Total Marine Fisheries Catches for the New Hebrides and the Republic of Vanuatu, 1950–2014 - Marc Léopold; Gilbert David; Jason Raubani; Jeremie Kaltavara; Lincoln Hood; Dirk Zeller (Frontiers in Marine Science, 2017)

Post-diagnosis serum insulin-like growth factors in relation to dietary and lifestyle changes in the Prostate testing for cancer and Treatment (ProtecT) trial - Vanessa Er; Kalina Biernacka; Andrew J. Simpkin; Richard M. Martin; Mona Jeffreys; Pauline Emmett; Rebecca Gilbert; Kerry N. L. Avery; Eleanor Walsh; Michael Davis; Jenny L. Donovan; David E. Neal; et al. (Cancer Causes & Control, 2017)
Purpose The insulin-like growth factor (IGF) system is modifiable by diet and lifestyle, and has been linked to prostate cancer development and progression. Methods We conducted a prospective cohort study of 621 men diagnosed with localized prostate cancer to investigate the associations of dietary and lifestyle changes with post-diagnosis circulating levels of IGF-I and IGFBP-3. We used analysis of covariance to estimate the associations, controlling for baseline IGF-I or IGFBP-3, respectively. Results Mean IGF-I levels were 6.5% (95% CI −12.8, −0.3%, p = 0.04) lower in men who decreased their protein intake after diagnosis compared to men who did not change. Men who changed their fruit and vegetable intake had lower IGF-I levels compared to non-changers [Decreased intake: −10.1%, 95% CI −18.4, −1.8%, p = 0.02; Increased intake: −12.0%, 95% CI −18.4, −1.8%, p = 0.002]. IGFBP-3 was 14.6% (95% CI −24.5, −4.8%, p = 0.004) lower in men who achieved a healthy body mass index after diagnosis. Men who became inactive had 9.5% higher average IGF-I levels (95% CI 0.1, 18.9%, p = 0.05). Conclusions Decreased protein intake and body mass index, and increased physical activity and fruit and vegetable intake, following a prostate cancer diagnosis were associated with reduced post-diagnosis serum IGF-I and IGFBP-3. Counterintuitively, reduced fruit and vegetable intake was also associated with reduced IGF-I, but with weak statistical support, possibly implicating chance. If confirmed in other studies, our findings may inform potential lifestyle interventions in prostate cancer. ProtecT was registered at International Standard Randomised Controlled Trial Registry, http://isrctn.org as ISRCTN20141297.

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

Quantifying rapid spatial and temporal variations of CO2 fluxes from small, lowland freshwater ponds - Peter J. Gilbert; David A. Cooke; Michael Deary; Scott Taylor; Michael J. Jeffries (Hydrobiologia, 2017)

Negative affect subtypes and craving differentially predict long-term cessation success among smokers achieving initial abstinence - Yantao Zuo; Norka E. Rabinovich; David G. Gilbert (Psychopharmacology, 2017)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

A poor international standard for trap selectivity threatens carnivore conservation - Emilio Virgós; Jorge Lozano; Sara Cabezas-Díaz; David W. Macdonald; Andrzej Zalewski; Juan Carlos Atienza; Gilbert Proulx; William J. Ripple; Luis M. Rosalino; Margarida Santos-Reis; Paul J. Johnson; Aurelio F. Malo; et al. (Biodiversity and Conservation, 2016)

Remembering Jerry Lwanga: A Perspective from His Colleagues - Tony L. Goldberg; Samuel Angedakin; Gilbert M. Isabirye Basuta; Michelle Brown; Thomas M. Butynski; Colin A. Chapman; Lauren Chapman; Sholly Gunter; Innocent Kato; Jean-Michel Krief; Sabrina Krief; Joanna E. Lambert; et al. (International Journal of Primatology, 2016)

Preparation of legionaminic acid analogs of sialo-glycoconjugates by means of mammalian sialyltransferases - David C. Watson; Warren W. Wakarchuk; Christian Gervais; Yves Durocher; Anna Robotham; Steve M. Fernandes; Ronald L. Schnaar; N. Martin Young; Michel Gilbert (Glycoconjugate Journal, 2015)

Network analysis of host–virus communities in bats and rodents reveals determinants of cross‐species transmission - Angela D. Luis; Thomas J. O'Shea; David T. S. Hayman; James L. N. Wood; Andrew A. Cunningham; Amy T. Gilbert; James N. Mills; Colleen T. Webb (Ecology Letters, 2015)
Bats are natural reservoirs of several important emerging viruses. Cross‐species transmission appears to be quite common among bats, which may contribute to their unique reservoir potential. Therefore, understanding the importance of bats as reservoirs requires examining them in a community context rather than concentrating on individual species. Here, we use a network approach to identify ecological and biological correlates of cross‐species virus transmission in bats and rodents, another important host group. We show that given our current knowledge the bat viral sharing network is more connected than the rodent network, suggesting viruses may pass more easily between bat species. We identify host traits associated with important reservoir species: gregarious bats are more likely to share more viruses and bats which migrate regionally are important for spreading viruses through the network. We identify multiple communities of viral sharing within bats and rodents and highlight potential species traits that can help guide studies of novel pathogen emergence.

Road mortality potentially responsible for billions of pollinating insect deaths annually - James H. Baxter-Gilbert; Julia L. Riley; Christopher J. H. Neufeld; Jacqueline D. Litzgus; David Lesbarrères (Journal of Insect Conservation, 2015)

Elevated rates of mild cognitive impairment in HIV disease - David P. Sheppard; Jennifer E. Iudicello; Mark W. Bondi; Katie L. Doyle; Erin E. Morgan; Paul J. Massman; Paul E. Gilbert; Steven Paul Woods (Journal of NeuroVirology, 2015)

Arsenic hazard in Cambodian rice from a market-based survey with a case study of Preak Russey village, Kandal Province - Peter J. Gilbert; David A. Polya; David A. Cooke (Environmental Geochemistry and Health, 2015)

Regulatory toxicology in the twenty-first century: challenges, perspectives and possible solutions - Tewes Tralau; Michael Oelgeschläger; Rainer Gürtler; Gerhard Heinemeyer; Matthias Herzler; Thomas Höfer; Heike Itter; Thomas Kuhl; Nikola Lange; Nicole Lorenz; Christine Müller-Graf; Ulrike Pabel; et al. (Archives of Toxicology, 2015)

Associations of vitamin D pathway genes with circulating 25-hydroxyvitamin-D, 1,25-dihydroxyvitamin-D, and prostate cancer: a nested case–control study - Rebecca Gilbert; Carolina Bonilla; Chris Metcalfe; Sarah Lewis; David M. Evans; William D. Fraser; John P. Kemp; Jenny L. Donovan; Freddie C. Hamdy; David E. Neal; J. Athene Lane; George Davey Smith; et al. (Cancer Causes & Control, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Post-glacial time series of explosive eruptions and associated changes in the magma plumbing system of Lonquimay volcano, south central Chile - David Gilbert; Armin Freundt; Steffen Kutterolf; Cosima Burkert (International Journal of Earth Sciences, 2014)

A bioenergetic framework for the temperature dependence of trophic interactions - Benjamin Gilbert; Tyler D. Tunney; Kevin S. McCann; John P. DeLong; David A. Vasseur; Van Savage; Jonathan B. Shurin; Anthony I. Dell; Brandon T. Barton; Christopher D.G. Harley; Heather M. Kharouba; Pavel Kratina; et al. (Ecology Letters, 2014)
Changing temperature can substantially shift ecological communities by altering the strength and stability of trophic interactions. Because many ecological rates are constrained by temperature, new approaches are required to understand how simultaneous changes in multiple rates alter the relative performance of species and their trophic interactions. We develop an energetic approach to identify the relationship between biomass fluxes and standing biomass across trophic levels. Our approach links ecological rates and trophic dynamics to measure temperature‐dependent changes to the strength of trophic interactions and determine how these changes alter food web stability. It accomplishes this by using biomass as a common energetic currency and isolating three temperature‐dependent processes that are common to all consumer–resource interactions: biomass accumulation of the resource, resource consumption and consumer mortality. Using this framework, we clarify when and how temperature alters consumer to resource biomass ratios, equilibrium resilience, consumer variability, extinction risk and transient vs. equilibrium dynamics. Finally, we characterise key asymmetries in species responses to temperature that produce these distinct dynamic behaviours and identify when they are likely to emerge. Overall, our framework provides a mechanistic and more unified understanding of the temperature dependence of trophic dynamics in terms of ecological rates, biomass ratios and stability.

Thermoregulatory responses during thermal acclimation in pigs divergently selected for residual feed intake - Paulo Henrique Reis Furtado Campos; Jean Noblet; Yolande Jaguelin-Peyraud; Hélène Gilbert; Pierre Mormède; Rita Flavia Miranda de Oliveira Donzele; Juarez Lopes Donzele; David Renaudeau (International Journal of Biometeorology, 2014)

Genome-wide association study and meta-analysis of intraocular pressure - A. Bilge Ozel; Sayoko E. Moroi; David M. Reed; Melisa Nika; Caroline M. Schmidt; Sara Akbari; Kathleen Scott; Frank Rozsa; Hemant Pawar; David C. Musch; Paul R. Lichter; Doug Gaasterland; et al. (Human Genetics, 2014)

Understanding the Needs of Colorectal Cancer Patients during the Pre-diagnosis Phase - David Wiljer; Tara Walton; Julie Gilbert; Amy Boucher; Peter M Ellis; Susan Schiff; Scott M Sellick; Marko Simunovic; Erin Kennedy; Sara Urowitz (Journal of Cancer Education, 2013)

Underground signals carried through common mycelial networks warn neighbouring plants of aphid attack - Zdenka Babikova; Lucy Gilbert; Toby J. A. Bruce; Michael Birkett; John C. Caulfield; Christine Woodcock; John A. Pickett; David Johnson (Ecology Letters, 2013)
The roots of most land plants are colonised by mycorrhizal fungi that provide mineral nutrients in exchange for carbon. Here, we show that mycorrhizal mycelia can also act as a conduit for signalling between plants, acting as an early warning system for herbivore attack. Insect herbivory causes systemic changes in the production of plant volatiles, particularly methyl salicylate, making bean plants, Vicia faba , repellent to aphids but attractive to aphid enemies such as parasitoids. We demonstrate that these effects can also occur in aphid‐free plants but only when they are connected to aphid‐infested plants via a common mycorrhizal mycelial network. This underground messaging system allows neighbouring plants to invoke herbivore defences before attack. Our findings demonstrate that common mycorrhizal mycelial networks can determine the outcome of multitrophic interactions by communicating information on herbivore attack between plants, thereby influencing the behaviour of both herbivores and their natural enemies.

Men with prostate cancer make positive dietary changes following diagnosis and treatment - Kerry N. L. Avery; Jenny L. Donovan; Rebecca Gilbert; Michael Davis; Pauline Emmett; Liz Down; Steven Oliver; David E. Neal; Freddie C. Hamdy; J. Athene Lane (Cancer Causes & Control, 2013)

Carbon footprint initiative in Uganda - Paul Walakira; Jackson Gilbert Majaliwa Mwanjalolo; David Mfitumukiza; Phenny H. Dentons Kaviiri (The International Journal of Life Cycle Assessment, 2013)

Nicotine differentially modulates antisaccade eye-gaze away from emotional stimuli in nonsmokers stratified by pre-task baseline performance - Nathaniel J. Wachter; David G. Gilbert (Psychopharmacology, 2013)

Associations of circulating retinol, vitamin E, and 1,25-dihydroxyvitamin D with prostate cancer diagnosis, stage, and grade - Rebecca Gilbert; Chris Metcalfe; William D. Fraser; Jenny Donovan; Freddie Hamdy; David E. Neal; J. Athene Lane; Richard M. Martin (Cancer Causes & Control, 2012)

Comment on sea lion population viability analysis - Paul A. Breen; David J. Gilbert; Paul J. Starr (Polar Biology, 2012)

Mind the gap: a comparative study of migratory behavior in social amoebae - Owen M. Gilbert; Jennie J. Kuzdzal-Fick; David C. Queller; Joan E. Strassmann (Behavioral Ecology and Sociobiology, 2012)

Understanding the needs of lung cancer patients during the pre-diagnosis phase - David Wiljer; Tara Walton; Julie Gilbert; Amy Boucher; Peter M Ellis; Susan Schiff; Scott M Sellick; Marko Simunovic; Andrea Bezjak; Sara Urowitz (Journal of Cancer Education, 2012)

A cross-sectional analysis of the association between diet and insulin-like growth factor (IGF)-I, IGF-II, IGF-binding protein (IGFBP)-2, and IGFBP-3 in men in the United Kingdom - Nicholas J. Young; Chris Metcalfe; David Gunnell; Mari-Anne Rowlands; J. Athene Lane; Rebecca Gilbert; Kerry N. L. Avery; Michael Davis; David E. Neal; Freddie C. Hamdy; Jenny Donovan; Richard M. Martin; et al. (Cancer Causes & Control, 2012)

Lemming winter habitat choice: a snow-fencing experiment - Donald G. Reid; Frédéric Bilodeau; Charles J. Krebs; Gilles Gauthier; Alice J. Kenney; B. Scott Gilbert; Maria C.-Y. Leung; David Duchesne; Elizabeth Hofer (Oecologia, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Predictors of 25-hydroxyvitamin D and its association with risk factors for prostate cancer: evidence from the Prostate testing for cancer and Treatment study - Rebecca Gilbert; Richard M. Martin; William D. Fraser; Sarah Lewis; Jenny Donovan; Freddie Hamdy; David E. Neal; J. Athene Lane; Chris Metcalfe (Cancer Causes & Control, 2012)

Feeder layer- and animal product-free culture of neonatal foreskin keratinocytes: improved performance, usability, quality and safety - Peter De Corte; Gunther Verween; Gilbert Verbeken; Thomas Rose; Serge Jennes; Arlette De Coninck; Diane Roseeuw; Alain Vanderkelen; Eric Kets; David Haddow; Jean-Paul Pirnay (Cell and Tissue Banking, 2012)

Spatial gradients of methylmercury for breeding common loons in the Laurentian Great Lakes region - David C. Evers; Kathryn A. Williams; Michael W. Meyer; Anton M. Scheuhammer; Nina Schoch; Andrew T. Gilbert; Lori Siegel; Robert J. Taylor; Robert Poppenga; Christopher R. Perkins (Ecotoxicology, 2011)

The Human Dimensions of Coastal and Marine Ecosystems in the Western Indian Ocean - Joshua E. Cinner; Gilbert David (Coastal Management, 2011)

Measuring Recreational Fishers’ Social Acceptance of the Natural Marine Reserve of Reunion Island - Aurélie Thomassin; Gilbert David; Julie Duchêne; Claire Bissery (Coastal Management, 2011)

The combined effect of waterlogging, extractable P and soil pH on α-diversity: a case study on mesotrophic grasslands in the UK - Dana Michalcová; Joanne C. Gilbert; Clare S. Lawson; David J. G. Gowing; Rob H. Marrs (Plant Ecology, 2011)

Rapid Intradermal Delivery of Liquid Formulations Using a Hollow Microstructured Array - Scott A. Burton; Chin-Yee Ng; Ryan Simmers; Craig Moeckly; David Brandwein; Tom Gilbert; Nathan Johnson; Ken Brown; Tesha Alston; Gayatri Prochnow; Kris Siebenaler; Kris Hansen (Pharmaceutical Research, 2011)

The relation between adiposity throughout the life course and variation in IGFs and IGFBPs: evidence from the ProtecT (Prostate testing for cancer and Treatment) study - Mari-Anne Rowlands; Jeff M. P. Holly; David Gunnell; Rebecca Gilbert; Jenny Donovan; J. Athene Lane; Gemma Marsden; Simon M. Collin; Freddie Hamdy; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2010)

A multidisciplinary study of archaeological grape seeds - Enrico Cappellini; M. Thomas P. Gilbert; Filippo Geuna; Girolamo Fiorentino; Allan Hall; Jane Thomas-Oates; Peter D. Ashton; David A. Ashford; Paul Arthur; Paula F. Campos; Johan Kool; Eske Willerslev; et al. (The Science of Nature, 2010)

Domain-wide regulation of DNA replication timing during mammalian development - Benjamin D. Pope; Ichiro Hiratani; David M. Gilbert (Chromosome Research, 2010)

The role of surface energy and water wettability in aminoalkyl/fluorocarbon/hydrocarbon-modified xerogel surfaces in the control of marine biofouling - Stephanie M. Bennett; John A. Finlay; Nikhil Gunari; David D. Wells; Anne E. Meyer; Gilbert C. Walker; Maureen E. Callow; James A. Callow; Frank V. Bright; Michael R. Detty (Biofouling, 2009)

Palaeoenvironment reconstruction, volcanic evolution and geochronology of the Cerro Blanco subcomplex, Nevados de Chillán volcanic complex, central Chile - Katy Mee; Jennie S. Gilbert; David W. McGarvie; José A. Naranjo; Malcolm S. Pringle (Bulletin of Volcanology, 2009)

Effects of nicotine on novelty detection and memory recognition performance: double-blind, placebo-controlled studies of smokers and nonsmokers - Brett Froeliger; David G. Gilbert; F. Joseph McClernon (Psychopharmacology, 2009)

Discovery of a large clonal patch of a social amoeba: implications for social evolution - OWEN M GILBERT; DAVID C QUELLER; JOAN E STRASSMANN (Molecular Ecology, 2009)
Studies of genetic population structures of clonally reproducing macro‐organisms have revealed large areas where only one clone is found. These areas, referred to as clonal patches, have not been shown to occur in free‐living microbes until now. In free‐living microbes, high genetic diversity at local scales is usually maintained by high rates of dispersal. We report, however, a highly dense, 12‐m clonal patch of the social amoeba Dictyostelium discoideum in a cattle pasture located in a Texas Gulf Coast prairie. We confirm the presence of only one clone by the analysis of 65 samples and amplification of 10 polymorphic microsatellite loci. Samplings of additional cattle pastures nearby showed higher clonal diversity, but with a density of D. discoideum isolates lower than in the clonal patch. These findings show that high rates of microbial dispersal do not always produce genetic diversity at local scales, contrary to the findings of previous studies. The existence of clonal patches may be particularly important for microbial social evolution.

Large rivers do not always act as species barriers for Lepilemur sp. - Mathias Craul; Ute Radespiel; David W. Rasolofoson; Gilbert Rakotondratsimba; Odon Rakotonirainy; Solofonirina Rasoloharijaona; Blanchard Randrianambinina; Jonah Ratsimbazafy; Felix Ratelolahy; Tahirihasina Randrianamboavaonjy; Lucien Rakotozafy (Primates, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Mission-Specific Platforms for the Integrated Ocean Drilling Program - Dan Evans; Gilbert Camoin; David McInroy; Alister Skinner (Oceanography, 2006)

Subglacial and ice-contact volcanism at the Öræfajökull stratovolcano, Iceland - John A. Stevenson; David W. McGarvie; John L. Smellie; Jennie S. Gilbert (Bulletin of Volcanology, 2006)

Pharmacologic and Pharmacokinetic Assessment of Anti-TGFβ2 Aptamers in Rabbit Plasma and Aqueous Humor - Thomas G. McCauley; Jeffrey C. Kurz; Patricia G. Merlino; Scott D. Lewis; Madaline Gilbert; David M. Epstein; H. Nicholas Marsh (Pharmaceutical Research, 2006)

SNPs in the neural cell adhesion molecule 1 gene (NCAM1) may be associated with human neural tube defects - Kristen L. Deak; Abee L. Boyles; Heather C. Etchevers; Elizabeth C. Melvin; Deborah G. Siegel; Felicia L. Graham; Susan H. Slifer; David S. Enterline; Timothy M. George; Michel Vekemans; David McClay; Alexander G. Bassuk; et al. (Human Genetics, 2005)

Remote sensing as a tool for achieving and monitoring progress toward sustainability - Gilbert L. Rochon; Chris J. Johannsen; David A. Landgrebe; Bernard A. Engel; Jonathan M. Harbor; Sarada Majumder; Larry L. Biehl (Clean Technologies and Environmental Policy, 2003)

Mating Behavior, Sexual Selection, and Copulatory Courtship in a Promiscuous Beetle - David Shuker; Nick Bateson; Heidi Breitsprecher; Rebecca O'Donovan; Helen Taylor; Chris Barnard; Jerzy Behnke; Sarah Collins; Francis Gilbert (Journal of Insect Behavior, 2002)

Effects of seedling size, El Niño drought, seedling density, and distance to nearest conspecific adult on 6-year survival of Ocotea whitei seedlings in Panamá - Gregory S. Gilbert; Kyle E. Harms; David N. Hamill; Stephen P. Hubbell (Oecologia, 2001)

The effect of fenofibrate treatment on endothelium-dependent relaxation induced by oxidative modified low density lipoprotein from hyperlipidemic patients - Binhua Liang; Jason C. McMaster; Edwin A. Kroeger; Grant M. Hatch; David Mymin; Tom Dembinski; Gilbert Arthur; Garry Shen; Ricky Y.K. Man; Patrick C. Choy (Molecular and Cellular Biochemistry, 2000)

Purification and characterization of the recombinant CMP-sialic acid synthetase from Neisseria meningitidis - Michel Gilbert; David C. Watson; Warren W. Wakarchuk (Biotechnology Letters, 1997)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)